Biomedicine and beatitude : an introduction to Catholic bioethics - Austriaco, Nicanor Pier Giorgio (Catholic moral thought., 2021)
"Comprehensive overview of Catholic teaching on practical issues in modern medicine and bioethics. This second edition includes a new chapter on bodily modifications and a series of new figures, as well as bringing the original text up to date in light of the teachings of Pope Francis and recent events such as the COVID-19 pandemic"--